A comparison of the flavonoids in Athyriaceae and Aspleniaceae - Umikalsom, Y.; Grayer-Barkmeijer, Renée J.; Harborne, Jeffrey B. (1994)
Flavonoid patterns were examined for 18 species of Athyriaceae and 15 species of Aspleniaceae, mainly of Malaysian origin. In the Athyriaceae, flavonol 3-O-glycosides based on both quercetin and kaempferol were the most common flavonoids found, and additionally in some species of Diplazium and Deparia flavone C-glycosides were detected, based on apigenin. Flavonoid data supports the generic separation of Athyrium, Diplazium and Deparia based on morphological and other characters. In the Aspleniaceae, the flavonoid profiles are more complex. As to flavonols, kaempferol derivatives appeared to predominate, especially the 3,7-glycosides, but 3,4′-diglycosides and 3,7,4′-triglycosides were also detected. O-Methylated kaempferol glycosides were found in A. marinum. Flavone C-glycosides were based on both luteolin and apigenin, and the C-sugars were sometimes O-glycosylated. In three species of Asplenium, flavone O-glycosides were encountered, including scutellarein 6-O-glucoside in A. belangeri. Thus the overall tendency of the flavonoid chemistry of the Aspleniaceae is different from that of the Athyriaceae, and this supports the taxonomic separation of the two families. © 1994.